2017
DOI: 10.2514/1.b36425
|View full text |Cite
|
Sign up to set email alerts
|

Transient Computational Thermofluid-Dynamic Simulation of Hybrid Rocket Internal Ballistics

Abstract: A computational thermofluid-dynamic model of hybrid rocket internal ballistics is developed. Numerical simulations of the flowfield in a laboratory small-scale hybrid rocket motor, operated with gaseous oxygen and high-density polyethylene propellants, are carried out with the aim of predicting the solid fuel regression rate experimentally achieved with two different oxidizer injectors. The fuel regression rate is the main parameter for the hybrid rocket design. Here, it is calculated with a detailed gas/surfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 31 publications
0
20
0
Order By: Relevance
“…According to literature, several approaches have been adopted for radiation modelling. In most studies on fuel regression rate hybrid rockets, radiation is neglected ( [14][15][16][17][18][19]) assuming that this phenomenon would be significant only for metallized fuels. However Chiaverini et al [7] have shown that for relatively low oxidant flows, radiation could have a significant effect on the fuel regression rate even though the importance of this effect is particularly controverted in the literature.…”
Section: B Radiation Models Employed In Computational Fluid Dynamicsmentioning
confidence: 99%
“…According to literature, several approaches have been adopted for radiation modelling. In most studies on fuel regression rate hybrid rockets, radiation is neglected ( [14][15][16][17][18][19]) assuming that this phenomenon would be significant only for metallized fuels. However Chiaverini et al [7] have shown that for relatively low oxidant flows, radiation could have a significant effect on the fuel regression rate even though the importance of this effect is particularly controverted in the literature.…”
Section: B Radiation Models Employed In Computational Fluid Dynamicsmentioning
confidence: 99%
“…Indeed, the extension of those models to new motors that can be different in geometry, scale, etc., is hardly possible without the availability of existing experimental data for each motor. For these reasons, there is a renewed interest in the development of more accurate and advanced models based on Computational Fluid Dynamics (CFD) [3][4][5][6][7][8][9][10][11][12][13][14][15] that are capable of representing more accurately the physico-chemical phenomena involved. The numerical modeling of the fluid dynamics and the combustion process in the fuel port area and nozzle of a hybrid rocket is a challenging task as it involves strongly-interacting multiphysics processes such as fluid dynamics, fuel pyrolysis [16,17], atomization and vaporization of the oxidizer, mixing and combustion in the gas phase [11][12][13]18], thermochemical erosion of the nozzle [3,19], particulate formation, and the radiative characteristics of the flame.…”
Section: Introductionmentioning
confidence: 99%
“…Commercial CFD tools are generally not optimized to this task, as they are typically less flexible for the treatment of fluid/solid boundary conditions, which are typically prescribed as constant temperature or heat flux with no feedback with the mass transfer mechanisms (pyrolysis, sublimation, etc.). To obtain an adequate tool for the analysis of the flowfield of hybrid rocket burning classical non-liquefying fuels, CFD codes should take into account spatially-varying heat flux, surface temperature, and fuel regression rate, realistic surface multispecies mass and energy balances, thermal soak into the fuel grain, radiative energy exchange, and finite-rate Arrhenius kinetics for fuel pyrolysis modeling or, in the case of commercial solvers, a number of user-defined functions need to be built and integrated in the numerical framework [8,14,20]. In the most general case, an in-house code has to be used.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations